An Effective Time Table Generation System with Reminder Alerts for Cloud Environment - Reddy, D. Siva Sankara (International Journal of Psychosocial Rehabilitation, 2020)
Timetable generation is done based on all the possible constraints in the college environments, including the availability of classrooms, staff members, labs availability and all other infrastructural needs. The main focus is given to the case in which the same faculty is handling different subject for various classes. The HOD (Admin) through his login provides the resource availability as inputs and has the authority for generating timetable. The staff members using their login can view only their schedule. Timetable generation is done using the heuristic algorithm. The system will be shared through the cloud server. This system is developed on ASP.Net environment and MySQL.